2023
DOI: 10.3904/kjim.2022.249
|View full text |Cite
|
Sign up to set email alerts
|

Long-term cardiovascular events in hypertensive patients: full report of the Korean Hypertension Cohort

Abstract: Background/Aims: This study evaluated the long-term cardiovascular complications among Korean patients with hypertension and compared them with that of controls without hypertension. Methods: The Korean Hypertension Cohort (KHC) enrolled 11,043 patients with hypertension and followed them for more than 10 years. Age-and sex-matched controls without hypertension were enrolled at a 1:10 ratio. We compared the incidence of cardiovascular events and death among patients and controls without hypertension. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…The patients’ PCI status was ascertained using the following procedure codes: M6551-M6554, M6561-M6566, M6572, and M6572 11 . Hypertension was defined as a SBP of ≥140 mmHg or DBP of ≥90 mmHg recorded in the health examination or the use of antihypertensive medications combined with the ICD-10 codes (I10-13, I15) 12 . Dyslipidemia was defined as an ICD-10 code of E78 and a history of lipid-lowering drug use or a total serum cholesterol level ≥240 mg/dL recorded in the health examination database 13 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The patients’ PCI status was ascertained using the following procedure codes: M6551-M6554, M6561-M6566, M6572, and M6572 11 . Hypertension was defined as a SBP of ≥140 mmHg or DBP of ≥90 mmHg recorded in the health examination or the use of antihypertensive medications combined with the ICD-10 codes (I10-13, I15) 12 . Dyslipidemia was defined as an ICD-10 code of E78 and a history of lipid-lowering drug use or a total serum cholesterol level ≥240 mg/dL recorded in the health examination database 13 .…”
Section: Methodsmentioning
confidence: 99%
“…The patients' PCI status was ascertained using the following procedure codes: M6551-M6554, M6561-M6566, M6572, and M6572 11 . Hypertension was defined as a SBP of 140 mmHg or DBP of 90 mmHg recorded in the health examination or the use of antihypertensive medications combined with the ICD-10 codes (I10-13, I15) 12 .…”
Section: Definition Of T2dm Comorbidities and Clinical Parametersmentioning
confidence: 99%
“…A post‐hoc analysis was conducted with subgroups of age, sex, and cardiovascular risks to adjust for potential selection bias. The detailed statistical analysis method has been described previously 12,13 . Statistical analyses were performed using SAS (version 9.4, SAS Institute, Cary, NC) and R software (version 4.0.3; R project).…”
Section: Methodsmentioning
confidence: 99%
“…The matched variables were sex and age, on a case‐to‐case basis. The full results have been previously published 12–14 . The study protocols were reviewed and approved by the Institutional Review Boards of each participating hospital, including the coordinating center (H‐1810‐056‐977), and the need to obtain informed consent from patients was waived prior to patient enrollment.…”
Section: Methodsmentioning
confidence: 99%
“…Lee et al [ 1 ] reported long-term cardiovascular (CV) events in a multi-center clinical hypertension cohort, stating that the overall CV event rate was 15%, thus 19.4%, 13.3%, and 11.2% in high-, moderate-, and low-risk groups, respectively. The operational definitions of the CV risk groups are not fully consistent with the current guidelines.…”
mentioning
confidence: 99%